Highlights on artificial insemination (AI) technology in the pig - Tarek Khalifa (Macedonian Veterinary Review, 2014)
Over the past decade, there has been a tremendous increase in the development of field AI services in the majority of countries concerned with pig production. The objective of this paper is to review: (a) the current status of swine AI in the world, (b) significance and limitation of AI with liquid and frozen semen, (c) the biological traits of porcine semen in relation to in-vitro sperm storage, (d) the criteria used for selection of a boar stud as a semen supplier, (e) how to process boar semen for liquid and frozen storage in the commercial settings and (f) how to improve fertility and prolificacy of boar semen. More than 99% of the inseminations conducted worldwide are made with liquid-stored semen. AI with frozen semen is used only for upgrading the genetic base in a particular country or herd. Determining the initial quality of semen ejaculates along with the selection of the optimum storage extender has a profound effect on the quality and fertility of AI doses. Different procedures have been used for improving the fertility of preserved spermatozoa including colloidal centrifugation of the semen, intrauterine insemination and modulation of the uterine defense mechanism after AI. Development of an efficient protocol for synchronizing the time of ovulation in sows and gilts coupled with improving uterine horn insemination technique will make a breakthrough in the commercial use of frozen boar semen.